Heróis da luz: desenvolvimento de um jogo sério para auxiliar o ensino de suporte básico de vida - MENDES, Ingrid Nery (Universidade Federal do Pará, 2024)
Games not only provide entertainment and fun but can also play a significant role in assimilating and reinforcing specific knowledge. This leads us to the category of serious games, which are designed to aid in the consolidation of content relevant to society. Basic Life Support is a protocol aimed at reversing Cardiopulmonary Arrest, acquired through specialized training. However, without regular proper practice, this knowledge can fade. Faced with this issue, the current software prototype uses game mechanics to propose a potential solution to this gap in human memory: the lack of consistent practice. Through a systematic mapping, the existence of a lacking market (and a scientific subfield) that demands more accessible solutions was identified, targeting Nursing students, first responders, and other healthcare professionals, all seeking to maintain this knowledge. This is especially crucial in places like the Brazilian territory and developing countries, where access to advanced and costly technologies is limited. The prototype was developed following the guidelines established by the Health Games research group at the Oswaldo Cruz Foundation. Thus, a game design document was elaborated, containing flowcharts, diagrams, and other elements that allowed the realization of this project, resulting in the creation of a digital serious game. The chosen game engine was Ren’Py, due to its emphasis on narratives, use of the Python programming language, and its open-source nature with a low implementation cost. Ultimately, this work served as an idea laboratory, enabling various experiences. This included the publication of three scientific papers and interaction with research groups from different regions of Brazil. It also resulted in new interpersonal, professional, and aca demic connections, providing learning across various dimensions of human understanding, especially on a personal and evolutionary level.